Genetic diversity of the cultured giant freshwater prawn (Macrobrachium rosenbergii) in China based on microsatellite markers. (April 2015) - Nguyen Thanh, Hai; Liu, Qigen; Zhao, Liangjie; Zhang, Hong; Liu, Jun
Abstract: The Giant freshwater prawn (GFP), Macrobrachium rosenbergii, is one of the most important crustacean species cultured in China, but information on the genetic diversity of GFP in China is still limited. In this study we analyzed the genetic diversity of 6 cultured GFP populations collected in China, and 2 wild populations from Viet Nam. The wild populations were included as a reference so that the genetic diversity of the introduced cultured GFP populations could be evaluated. We used six polymorphic primer pairs to estimate genetic diversity. Results showed that the number of alleles per locus ranged from 6 to 19. The mean observed heterozygosity (0.364 ± 0.090) was less than the expected heterozygosity (0.893 ± 0.016); highly significant deficiencies in heterozygotes were detected (100%). The polymorphism information content (PIC) of 8 populations at 6 loci was greater than 0.5 (varying from 0.616 to 0.912). Pair-wise genetic differentiation ( F ST ) varied from 0.006 to 0.129 among the eight populations. The dendrogram based on genetic distance showed six populations distributed on the same major branch, suggesting that they have closely genetic distance and two populations (ZJC and GDB) distributed on the other branch, so they also have closely genetic distance. The results of study provide a baseline assessment of genetic diversity in some populations in China and Viet Nam that will be useful for the development of breeding programmes in the future. Highlights: Genetic diversity of cultured populations of Giant freshwater prawn (GFP) in China. Microsatellite markers. Comparison genetic diversity between cultured and wild population of Giant freshwater prawn.